Clinical and socio-economic predictors of work participation in adult CHD patients. (2nd August 2020) - Sarno, Lauren A.; Cortright, Lindsay; Stanley, Tiara; Tumin, Dmitry; Li, Jennifer S.; Sang, Charlie J.
Abstract: Background: Adults with CHD have reduced work participation rates compared to adults without CHD. We aimed to quantify employment rate among adult CHD patients in a population-based registry and to describe factors and barriers associated with work participation. Methods: We retrospectively identified adults with employment information in the North Carolina Congenital Heart Defects Surveillance Network. Employment was defined as any paid work in a given year. Logistic regression was used to examine patients' employment status during each year. Results: The registry included 1, 208 adult CHD patients with a health care encounter between 2009 and 2013, of whom 1, 078 had ≥1 year of data with known employment status. Overall, 401 patients (37%) were employed in their most recent registry year. On multivariable analysis, the odds of employment decreased with older age and were lower for Black as compared to White patients (odds ratio = 0.78; 95% confidence interval: 0.62, 0.98; p = 0.030), and single as compared to married patients (odds ratio = 0.50; 95% confidence interval: 0.39, 0.63; p < 0.001). Conclusion: In a registry where employment status was routinely captured, only 37% of adult CHD patients aged 18–64 years were employed, with older patients, Black patients, and single patients being less likely to be employed. Further work is needed to consider how enhancing cardiology follow-up for adults with CHD can integrate support for employment.